Percentage of swimmer's coach needs for the development of applications for the physical conditions of swimming - Falaahudin, Ardhika; Suharjana, Suharjana; Sumarjo, Sumarjo (Quality in Sport, 2022)
Swimming is a great sport for keeping fit and fresh because it requires all parts of the body to remain actively moving in the water and because of the weight of the body's resistance to water. The trainer's inability to provide an understanding of physical exercise, design a training program, and comprehend the dosage of athlete training is the root cause of the athlete's diminished physical ability. The purpose of this research is to find out percentage of swimmer's coach needs for the development of applications for the physical conditions of swimming. A survey based quantitative descriptive approach is utilized in this study. The participants in this study were 5 Yogyakarta swimming club coaches. The total sampling method was used to select 5 club coaches for this study's sample. In this study, a questionnaire instrument with a Likert scale. The data in this study were analyzed using descriptive analysis with SPSS version 25. Based on the research results obtained data percentage of trainer needs regarding the application of the physical condition of swimming in the high category, obtaining a percentage of 80% with a total of 4 trainers and a moderate percentage of 20% consisting of 1 trainer. Therefore, it can be concluded that the swimmer's coach is highly dependent on the application of the swimming sport's physical condition.